Developmental cascade models linking peer victimization, depression, and academic achievement in Chinese children - Liu, Junsheng; Bullock, Amanda; Coplan, Robert J.; Chen, Xinyin; Li, Dan; Zhou, Ying (British journal of developmental psychology, 2018)
This study explored the longitudinal relations among peer victimization, depression, and academic achievement in Chinese primary school students. Participants were N = 945 fourth‐grade students (485 boys, 460 girls; Mage = 10.16 years, SD = 2 months) attending elementary schools in Shanghai, People's Republic of China. Three waves of data on peer victimization, depression, and academic achievement were collected from peer nominations, self‐reports, and school records, respectively. The results indicated that peer victimization had both direct and indirect effects on later depression and academic achievement. Depression also had both direct and indirect negative effects on later academic achievement, but demonstrated only an indirect effect on later peer victimization. Finally, academic achievement had both direct and indirect negative effects on later peer victimization and depression. The findings show that there are cross‐cultural similarities and differences in the various transactions that exist among peer victimization, depression, and academic achievement. Statement of contribution What is already known on this subject? Peer victimization directly and indirectly relates to depression and academic achievement. Depression directly and indirectly relates to academic achievement. Academic achievement directly and indirectly relates to depression. What the present study adds? A developmental cascade approach was used to assess the interrelations among peer victimization, depression, and academic achievement. Academic achievement mediates the relation between peer victimization and depression. Depression is related to peer victimization through academic achievement. Academic achievement directly and indirectly relates to peer victimization. Academic achievement is related to depression through peer victimization.